High‐definition television transmission at 600 GHz combining THz photonics hotspot and high‐sensitivity heterodyne receiver. Issue 5 (1st February 2014) - Ducournau, G.; Pavanello, F.; Beck, A.; Tohme, L.; Blin, S.; Nouvel, P.; Peytavit, E.; Zaknoune, M.; Szriftgiser, P.; Lampin, J.F.
Abstract : A 600 GHz data transmission using the combination of a photonic emission using a uni‐travelling carrier photodiode and an electronic detection is investigated. A high‐definition television transmission at this carrier frequency with a very low power at the receiver is reported. Only 10 nW of terahertz (THz) power at 600 GHz was sufficient to ensure a successful high‐definition video transmission. This combination of photonics at emission and heterodyne detection lead to achieving THz wireless links with a safe level of electromagnetic exposure.